COMPARATIVE STUDY OF PEAT HUMIC ACIDS BY USING UV SPECTROSCOPY - Purmalis, Oskars; Klavins, Maris (European Scientific Journal, ESJ, 2013)
Studies of the living organic matter humification process are essential for understanding of the carbon biogeochemical cycle. The aim of this study is to analyze relations between the properties of peat humic acids and peat humification degree using UV spectroscopy. The analysis has been done on samples of humic substances extracted from peat profiles in three ombrotrophic bogs and relations between peat age, decomposition and humification degree, botanical composition and properties of peat humic acids (elemental, functional composition) were studied. The found variability of peat properties is less significant than differences in the properties of peatforming living matter, thus revealing the dominant impact of humification process on the properties of peat. Correspondingly, composition of peat humic acids is little affected by differences in the composition of precursor living organic material. UV spectroscopy and used absorbance ratios can be successfully used for describing organic matter properties and diagenesis.